Pengaruh Pendidikan Kewarganegaraan Terhadap Partisipasi Politik Mahasiswa di Indonesia - Zebua, Magdalena Murniwati; Kurnia, Heni; Susilawati, Efi (CV. Kurnia Grup, 2025)
Student political participation is an important indicator of the sustainability of democracy in Indonesia. However, the low level of student involvement in political activities is a problem that requires attention. This study aims to analyze the influence of civic education on student political participation in Indonesia. Civic education is seen as one of the strategic instruments to increase political awareness of the younger generation. This study uses a quantitative survey method with a descriptive approach. Data were collected through questionnaires distributed to students from various universities in Indonesia. The results of the study indicate that civic education has a significant influence in increasing student political awareness and involvement. This awareness is reflected in their active participation in political activities, both on campus and off campus, such as joining student organizations, political discussions, and elections. The conclusion of this study confirms that strengthening the civic education curriculum is very necessary to produce a young generation that is politically aware and responsible as citizens.